ANALISIS MAJAS ELIPSIS DALAM AL-QUR’AN DAN FRASA BAHASA ARAB - Muhammad Afthon Ulin Nuha (Jurnal Bahasa Lingua Scientia, 2022)
Ellipsis is one of the phenomena of language structure that occurs to display a meaning by not mentioning all the pronunciation elements. The phenomenon of ellipsis occurs in many languages, including Arabic. In Arabic, even an ellipsis seems to contain several unique patterns, among others: there is a mandatory ellipsis, some are allowed to have ellipsis, and some are not allowed to have ellipsis. Departing from this problem, the writer considers it necessary to express thoughts about ellipsis in Arabic and will begin with Arabic phrases. By using the library research method, which is then processed using an inductive or deductive approach, it is hoped that it can produce conclusions about various ellipsis patterns in the Qur'an and Arabic phrases. In this study, it was also found that ellipsis on the Qur'an and Arabic phrases, in general, can be done if it does not cause ambiguity in meaning. Another value of the ellipsis is for the efficiency of word use, and more focus on the intended meaning.